ANALISIS KEANDALAN, KOORDINASI PROTEKSI. RELAY STANDBY EARTH FAULT (SBEF), SAAT TERJADI FAULT PADA GARDU INDUK MAROS - Yulianto, Bagas Tomi (Foristek, 2023)
The need for the use of electric power in modern times has experienced many developments in the field of technology, which of course has an effect on the amount of electricity consumed in society. Along with the rapid demand for electricity in Indonesia. The reliability of the electric power system is key to meeting the community's needs for electrical energy. This is due to the increasing number of human activities that require electrical energy. This study aims to analyze the reliability of protection coordination, working principles, security, and SBEF relay simulation when a fault occurs at the Maros substation. The method of data collection and direct observation in the field was carried out precisely at the Maros 150 kV Substation, the Maros Transmission and Substation Service Unit (ULTG). The results of the study, namely the reliability of the SBEF relay protection coordination when a fault occurs at the Maros substation, show that the first relay to work is the OCR GFR on the feeder side because, based on the working current settings and working time, if given a fault current of 3021 A, it will work after 426 ms, followed by the incoming side GFR OCR relay, SBEF stage 1 Fault percentage = 0075% so that it has a reliability percentage of 100%. The working principle and safeguards carried out on the SBEF relay when a fault occurs at the Maros substation and the data recap of the Maros ULTG fault can be seen by comparing the frequency of faults that cause the transformer to go out before and after the implementation of the two-stage SBEF relay function and the frequency of faults that cause the transformer to go out at ULTG Maros in 2019 as many as 1times and in 2020 as many as 0 times. The simulation on SBEF when a fault occurs at the Maros substation on the transformer uses the ETAP 19.0.1 application; the first time it works is GFR.